Professionalism In Principal Leadership Development Of Work Culture In Schools - Bahdin Nur Tanjung (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2020)
Educational staff have a very strategic role in shaping students' knowledge, skills and character. There for professional education staff will carry out their duties in a professional manner so as to produce higher quality graduates. Being a professional education staff will not be realized without any effort to improve it, while one way to make it happen is that the development of professionalism requires support from those who have an important role in this case is the principal, where the principal is a very important because the principal is directly related to the implementation of educational programs in schools.The achievement of educational goals is highly dependent on the leadership skills and wisdom of the principal who is one of the educational leaders. Because the principal is a professional official in a school organization whose job is to manage all of the organization's resources and work closely with the teacher in educating students to achieve educational goals. With the professionalism of the school principal, the development of teaching staff professionalism is made easy because according to their functions, the school principal understands the needs of the school he leads so that teacher competence does not only stagnate on the competencies he had before, but increases and develops well so that teacher professionalism will be realized.The research method by the author uses the systematic method Literature Review (SLR), by gathering several sources of information from journals, books and other articles. To improve the source of reading that will be produced by the reader later. Then after the sources are collected, the new author can conclude what results have been obtained from this reading source